2020
DOI: 10.1038/s41467-020-15147-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of functional synapse clusters on neuronal response selectivity

Abstract: Clustering of functionally similar synapses in dendrites is thought to affect neuronal inputoutput transformation by triggering local nonlinearities. However, neither the in vivo impact of synaptic clusters on somatic membrane potential (sVm), nor the rules of cluster formation are elucidated. We develop a computational approach to measure the effect of functional synaptic clusters on sVm response of biophysical model CA1 and L2/3 pyramidal neurons to in vivo-like inputs. We demonstrate that small synaptic clu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 78 publications
3
21
0
Order By: Relevance
“…By using randomly distributed inputs, our results suggest that functional synaptic clusters may emerge from potentiating neighboring synapses that each receive higher than average input. Our results are consistent with another modeling study investigating the impact of synaptic clustering on somatic membrane potential with in vivo-like conditions [ 93 ], which suggested that global plasticity rules would not be sufficient for formation of synaptic clusters. Our data-driven model of calcium dynamics accounts for global processes (produced by somatic spiking) and local processes (such as NMDA spikes), and the calcium-based synaptic plasticity rule can produce spatial clustering.…”
Section: Discussionsupporting
confidence: 92%
“…By using randomly distributed inputs, our results suggest that functional synaptic clusters may emerge from potentiating neighboring synapses that each receive higher than average input. Our results are consistent with another modeling study investigating the impact of synaptic clustering on somatic membrane potential with in vivo-like conditions [ 93 ], which suggested that global plasticity rules would not be sufficient for formation of synaptic clusters. Our data-driven model of calcium dynamics accounts for global processes (produced by somatic spiking) and local processes (such as NMDA spikes), and the calcium-based synaptic plasticity rule can produce spatial clustering.…”
Section: Discussionsupporting
confidence: 92%
“…Computational and in vitro studies indicate that 10–20 synchronized inputs are required to trigger dendritic spikes ( Ujfalussy and Makara, 2020 ). Existing in vivo studies, however, have found synchrony in only up to five neighboring dendritic spines, making it unclear what the impact of the synaptic clusters on the membrane potential of the posysynaptic neuron might be.…”
Section: Discussionmentioning
confidence: 99%
“…Dendrites can support information processing at multiple spatial scales ( ). On the local scale, i.e., the fine-scale organization of synapses over tens of microns, dendrites affect information processing by organizing synapses with similar properties into synaptic clusters that boost a neuron’s computational capacity through nonlinear integration ( ; , ; ; ; ). On the level of individual branches, dendrites exhibit dendritic maps in which the tuning of synapses (or synaptic clusters) varies systematically across the dendritic tree ( ; ; ; ; ).…”
Section: Organization Of Excitatory Synapsesmentioning
confidence: 99%